2011
DOI: 10.5559/di.20.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Big-Five Personality Dimensions and Speed of Information Processing Among Adolescents

Abstract: A developmental research of the relationship between the Big-Five and speed of information processing (SIP) was conducted with the aim of considering the personality-intelligence relationship. Personality dimensions were assessed by International Personality Item Pool (IPIP) questionnaire, while SIP and related test errors (Er--SIP) were assessed by Cognitive Abilities (KS2-2) pencil and paper perceptual speed test. The sample consisted of 1063 adolescents (378 males) at the age range from 14 to 18. The prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Highly extraverted individuals are attracted to positive messages, while highly neurotic individuals pay more attention to negative messages. Therefore, studies [ 42 , 43 ] have demonstrated that highly extraverted subjects interpret the same message differently from highly neurotic subjects. Future studies should be conducted by dividing respondents into two types—high level of extraversion and high level of neuroticism—to compare their gratifications obtained from news media, social media, and interpersonal communication to examine the effect of personality on information seeking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Highly extraverted individuals are attracted to positive messages, while highly neurotic individuals pay more attention to negative messages. Therefore, studies [ 42 , 43 ] have demonstrated that highly extraverted subjects interpret the same message differently from highly neurotic subjects. Future studies should be conducted by dividing respondents into two types—high level of extraversion and high level of neuroticism—to compare their gratifications obtained from news media, social media, and interpersonal communication to examine the effect of personality on information seeking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Dobne promjene čovjekova sustava obrade podataka i njihovu ulogu u kognitivnom razvoju proučavao je Žebec (2005). U proučavanju odnosa crta ličnosti i brzine obrade podataka utvrđeno je da se tijekom adolescencije ta brzina slabo mijenja i da u tome nema spolnih razlika (Žebec, Mlačić i Kopačević, 2011).…”
Section: Relevantna Obilježja Navedenog Razdobljaunclassified
“…The detrimental effects of noise have been widely observed in terms of hearing and non-hearing impairment, the most important of which are discomfort, sleep disorders, cardiovascular disease, and cognitive impairment, nerve stimulation, and stress. This has different effects depending on the level of exposure to noise and the tolerability of the person [5]. The Cognitive Processing Model (CPI) to assist the Differential Diagnostic Process.…”
Section: Introductionmentioning
confidence: 99%